Polyelectrolyte Complexation versus Ionotropic Gelation for Chitosan-Based Hydrogels with Carboxymethylcellulose, Carboxymethyl Starch, and Alginic Acid - Elizabeth Henao; Ezequiel Delgado; Héctor Contreras; Germán Quintana (International Journal of Chemical Engineering)
The preparation of gels by charge interaction methods has been extensively studied, but it is not yet clear how these methods influence gel characteristics. The objective of this work was to study differences in morphology and surface charge of hydrogels prepared by ionotropic gelation, polyelectrolyte complexation, and a combination of both methods. Thus, the anionic charge was provided by carboxymethylcellulose (CMC), carboxymethylated starch (CMS), and alginic acid (AA); calcium chloride (CaCl2) and chitosan (CS) were used for the ionotropic gelation and polyelectrolyte complexation, respectively. Those materials are commercially available, have low toxicity, and are widely used in the area. These compounds interact through physical crosslinks, which are affected by physical changes of the medium. Our results showed that these two methods produced changes in the morphology of the hydrogels. CMC gels exhibited larger pores in the presence of CaCl2. In polyelectrolyte complexation, CMS produced an increased agglomeration of particles, while the addition of CaCl2 to AA generated dispersed particles of size in the order of millimeters. Mixing both ionotropic gelation and polyelectrolyte complexation methods yielded gels of varied charge (568 mV for CMC, 502 mV for CMS, and 1713 mV for AA). FTIR spectra of the hydrogels showed interactions between the different polymeric compounds, being the greatest changes between 1250 and 1600 cm−1, due possibly to the replacement of Na by Ca at crosslinking points. Therefore, the method of gel preparation employed had a major influence on the size and pore distribution, parameters which in turn influence encapsulation and drug delivery in these systems.